Intermedial reference in literary works of Jan Bulhak - Petukhova , Marharyta V. (Journal of the Belarusian State University. Philology, 2020)
On the basis of literary works of Jan Bulhak (1876–1950) there are investigated the interactions of verbal (literature) and visual (photography) arts. The theory of intermediality stands out as one of the most effective approaches to the study of the problem of the interaction of arts. Two types of intermedial relationships are considered – extra-compositional and intra-compositional. Attention is focused on the phenomenon of a universalist author (multi-talented, Doppelbegabungen) – a creator who combines several practices (literature and painting, literature and music, photography and literature) in his artistic activity. There is shown the phenomenon of intermedial reference in the literary works of Jan Bulhak – the inclusion in the verbal space of the visual genres of portraiture, landscape and still life. It was revealed that in literary works the photo master models three types of portraits – genre, which characterizes the personality in connection with the social and professional environment; psychological, aimed at revealing the inner world of the hero; and staffage, when the portrait fits into the context of the landscape. It is noted that when creating landscape descriptions, Jan Bulhak uses the principles and techniques of visual arts (the principle of a photographic frame, a light motif, the panorama effect, the possibility of colorization) in the memoirs «The Land of Children» and in the travel essays out of cycle «Traveling the Photographer in a Word and Image». It is argued that the verbal still lifes in the memoirs «The Land of Children» affect not only the feelings of the reader (eyesight, hearing, smell, taste), but also reflect the whole cultural and historical layer – life and traditions of the szlachta court of the late 19th century.
Keywords: intermediality; verbal and visual; art interactions; multi-talent; universalist author; travel essays; memories; portrait; landscape; still life; motive